2022
DOI: 10.1177/13670069221075646
|View full text |Cite
|
Sign up to set email alerts
|

Mood and gender effects in emotional word processing in unbalanced bilinguals

Abstract: Aims and objectives: We aimed to explore the relationship between mood and emotional word processing in the bilingual context, as modulated by participants’ gender. Methodology: We presented mood-inducing film clips to 28 female and 28 male unbalanced Polish–English bilinguals to put them in positive and negative moods. Participants were asked to decide if native language (L1) and non-native language (L2) single words were positive, negative, or neutral (an emotive decision task). Data and analysis: We analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 99 publications
(170 reference statements)
0
12
0
Order By: Relevance
“…One of the outstanding questions in mood research concerns the possibility of gender differences in mood-language interactions. Federmeier et al (2001) was the first to report a stronger facilitatory effect of a positive mood on semantic processing in females than males, which was later corroborated in a recent behavioural study (Naranowicz et al, 2022a). Such a female advantage in a positive mood may possibly be explained by greater sensitivity to emotions (e.g., Goldstein et al, 2001) or increased physiological reactivity to affective stimuli (e.g., Bianchin and Angrilli, 2012;Naranowicz et al, 2022a).…”
Section: Other Future Research Directionsmentioning
confidence: 60%
See 4 more Smart Citations
“…One of the outstanding questions in mood research concerns the possibility of gender differences in mood-language interactions. Federmeier et al (2001) was the first to report a stronger facilitatory effect of a positive mood on semantic processing in females than males, which was later corroborated in a recent behavioural study (Naranowicz et al, 2022a). Such a female advantage in a positive mood may possibly be explained by greater sensitivity to emotions (e.g., Goldstein et al, 2001) or increased physiological reactivity to affective stimuli (e.g., Bianchin and Angrilli, 2012;Naranowicz et al, 2022a).…”
Section: Other Future Research Directionsmentioning
confidence: 60%
“…It has also been associated with the activation of a global, heuristics-based processing style during lexicosemantic access (Chwilla et al, 2011) and semantic re-analysis (Vissers et al, 2013). It is noteworthy that this effect may be limited to bilinguals' native language only (Naranowicz et al, 2022b) and observed mostly in females rather than males (Federmeier et al, 2001; see also Naranowicz et al, 2022a). Others have also suggested that a positive relative to negative mood may lead to increased motivation (Vissers et al, 2013) along with allocation of attentional resources to the most relevant contextual information (Vissers et al, 2013;Wang et al, 2016).…”
Section: Behavioural and Electrophysiological Evidencementioning
confidence: 96%
See 3 more Smart Citations